2017
DOI: 10.1007/s12603-016-0848-1
|View full text |Cite
|
Sign up to set email alerts
|

Iberian cured-ham consumption improves endothelial function in healthy subjects

Abstract: The present study demonstrates, for the first time, that regular consumption of ICH improves endothelial function in healthy adults. Strategies aimed to preserve or improve the endothelial function may have implications in vascular aging beyond the prevention of the atherothrombotic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The sample size was calculated using MedCalc v13 considering the PF as the main outcome during post-occlusive reactive hyperemia [5]. Based on data from previous studies of our group [28,29], we expected to find an increase in PF around 25%, from a baseline level of 60 ± 15 PU. Thus, to detect a significant difference of 15 PU in PF between the two interventions (i.e., purple garlic oil and placebo), a total of 52 participants (26 per group) were required, considering a statistical power of 80% and a confidence level of 95%.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated using MedCalc v13 considering the PF as the main outcome during post-occlusive reactive hyperemia [5]. Based on data from previous studies of our group [28,29], we expected to find an increase in PF around 25%, from a baseline level of 60 ± 15 PU. Thus, to detect a significant difference of 15 PU in PF between the two interventions (i.e., purple garlic oil and placebo), a total of 52 participants (26 per group) were required, considering a statistical power of 80% and a confidence level of 95%.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) conducted a study evaluating the arterial endothelium in 50 healthy subjects between 25 and 55 years of age, who consumed 50 g of ham daily for 6 weeks. In this study, they compared the effects of the consumption of Serrano ham and acorn‐fed Iberian ham, observing that the regular consumption of both was associated with cardiovascular benefits.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Studies have shown that in randomized controlled trials, eating dry-cured ham could reduce total cholesterol, low density lipoprotein, and glucose levels of healthy subjects, as well as improve endothelial function and help to prevent cardiovascular disease. [19,20] Recently, one research found that there was no obvious correlation between eating dry-cured ham and high blood pressure or weight gain, [21] and these influences can be attributed to the differences in protein profiles and metabolite profiles in dry-cured ham. Furthermore, different processing methods can affect the difference in protein profiles of ham.…”
Section: Introductionmentioning
confidence: 99%